2022
DOI: 10.3389/fmars.2022.1039824
|View full text |Cite
|
Sign up to set email alerts
|

Tropical cyclone Wind Pump induced chlorophyll-a enhancement in the South China Sea: A comparison of the open sea and continental shelf

Abstract: The continental shelf and open sea region have different ocean physical and environmental responses to tropical cyclones (TC). The present study firstly compared the grid-based maximum response (GMR) of sea surface chlorophyll a (Chl-a) to TCs Wind Pump between the continental shelf (depths 50-200m) and open sea (depths>200 m) region in the South China Sea (SCS) during 1998-2020, using multiple-satellite data. For all TC events, the average Chl-a increases by 0.13 mg/m3. The comparisons between the pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In general, the Cempaka-induced maximum Chla represented by SCSOFSv2 and MO and the Lupit-induced maximum Chla represented by MO were observed 2-3 days after the typhoon passed. This was 2 days ahead of the average (4-5 days) on the SCS shelf (Li and Tang, 2022), and several days ahead of the timing in the open sea, such as 6 days induced by Typhoon Linfa (Chen and Tang, 2012) and 13 days induced by Typhoon Nangka (Qiu et al, 2019). In addition, Cempaka-and Lupit-induced Chla bloom was significantly stronger than the approximate mean increase of 0.18 mg m −3 on the SCS shelf and 0.07 mg m −3 in the open sea, respectively (Li and Tang, 2022).…”
Section: Response Of Sea Surface Chlamentioning
confidence: 84%
See 3 more Smart Citations
“…In general, the Cempaka-induced maximum Chla represented by SCSOFSv2 and MO and the Lupit-induced maximum Chla represented by MO were observed 2-3 days after the typhoon passed. This was 2 days ahead of the average (4-5 days) on the SCS shelf (Li and Tang, 2022), and several days ahead of the timing in the open sea, such as 6 days induced by Typhoon Linfa (Chen and Tang, 2012) and 13 days induced by Typhoon Nangka (Qiu et al, 2019). In addition, Cempaka-and Lupit-induced Chla bloom was significantly stronger than the approximate mean increase of 0.18 mg m −3 on the SCS shelf and 0.07 mg m −3 in the open sea, respectively (Li and Tang, 2022).…”
Section: Response Of Sea Surface Chlamentioning
confidence: 84%
“…However, the southwest wind strengthened in the northern SCS during the Lupit period August 3-7, when compared to August 2, to produce a long-lasting vertical mixing and stronger upwelling along the continental shelf (Figure S7), uplifting more nutrients to stimulate a phytoplankton bloom and also Chla enhancement. Recent research has also found that slow-moving typhoons induce the most pronounced Chla increase on the continental shelf, consistent with that caused by strong and fast-moving typhoons (Li and Tang, 2022). Heavy rainfall and cloud coverage blocked the satellite observation of Chla during the Lupit period in the northern SCS (Figures 7I, L), so it cannot be used to verify the simulation results.…”
Section: Response Of Sea Surface Chlamentioning
confidence: 89%
See 2 more Smart Citations
“…At the same time, changes in TC-induced SSHA can be significant in nearshore regions. However, in open sea (e.g., WNPSO), TC movement is not controlled by such topography [12,[42][43][44]. These uncertainties in ML-based predictions may therefore be potentially influenced by the geographical location, in addition to being controlled by TC characteristics and preexisting ocean factors.…”
Section: Discussionmentioning
confidence: 99%